Meningkatkan Sinergitas Penyuluh Agama Hindu Dengan Prajuru Adat Di Bali - I Kadek Edi Palguna; I Gede Sutana (Maha Widya Duta : Jurnal Penerangan Agama, Pariwisata Budaya, dan Ilmu Komunikasi, 2020)
The majority of Balinese are Hindu with the Khayangan Tiga concept driven by the Pakraman village customary institution. During the pandemic, the ceremony was limited by referring to the appeal from the regional and central government to tolerate not to gather more than 25 people. This phenomenon then becomes the basis for raising the issue of problems in this paper related to the form of increased synergy carried out by Hindu religious instructors with Prajuru, and what are the factors for increasing the synergy of prajuru and extension personnel. The form of this increase is through Dharma Wecana and Dharma Tula through the internet network, along with Dharma Wecana videos on YouTube. The factors for increasing synergy are the attitude of the community in the application of religious teachings and the increase in the potential of the extension agents, one of which is by increasing the extension officers from an academic and non-academic perspective. Keyword: synergy, extension workers, and Prajuru Adat